Alkanes and alkanoic acids in the Beacon Supergroup samples from the Allan Hills and the Carapace Nunatak in Antarctica - Matsumoto, Genki I.; Funaki, Minoru; Machihara, Tsutomu; Watanuki, Kunihiko (1986)
P(論文) Alkanes and alkanoic acids in the Beacon Supergroup samples, sedimentary rocks, silicified wood and coal, from the Allan Hills and the Carapace Nunatak of southern Victoria Land in Antarctica were studied to elucidate the organic sources and sedimentary paleoenvironment. Normal alkanes ranging in carbon chain length from nC_<12> to nC_<30>, pristane and/or phytane were found in all the samples studied with concentrations ranging from 0.24 to 25μg/g of dry sample, along with near unity of carbon preference index (0.91-1.4). The major constituents were all short-chain n-alkanes (<C_<20>, nC_<16>, nC_<17>, nC_<18>, nC_<19>), pristane and/or phytane. Normal alkanoic acids of carbon chain lengths between nC_6 and nC_<28> were found in a sedimentary rock from the Carapace Nunatak and in silicified wood from the Allan Hills with low concentrations (2.3-25μg/g), together with the dominance of even-carbon numbers (carbon preference index, 1.6-2.8). The higher abundances of long-chain (≥nC_<20>) n-alkanes and n-alkanoic acids in the sedimentary rock from the Carapace Nunatak imply that the contribution of land plants to the sedimentary paleoenvironment of this area was greater than that in the Allan Hills. The pristane/phytane ratios suggest that the sedimentary paleoenvironment of the Allan Hills was oxic compared with that of the Carapace Nunatak. departmental bulletin paper